The linkage of training, knowledge management, and kaizen culture on the employee performance / Nurazree Mahmud … [et al.] - Mahmud, Nurazree; Mohamad, Maznita; Saadon, Nur Faziana; Johari, Siti Najwa (2023)
The study aims to determine the linkage of training, knowledge management, and Kaizen culture on the employee performance. The data utilized in this study is taken from primary sources, specifically questionnaires that were delivered to respondents through online Google forms as well as in a printed format. The population used in this study was a convenience sampling with a total sample of 113 respondents from selected private companies in Johor, Melaka and Negeri Sembilan. The study revealed that there was no statistically significant relationship between training and knowledge management, toward employee performance. The implementation of Kaizen culture in selected companies in the Southern region of Malaysia has a notable impact on employees performance. This study reveal the importance of kaizen culture in enhancing performance of employees. For instance, by applying the concept of kaizen, it directly will influence to several changes especially in the context of employee engagement, empowerment, better communication and employee recognition. Despite the existence of previous research on employee performance and its management antecedents, there is a lack of understanding regarding the connection between training, knowledge management, and the kaizen culture, particularly within the private sector in Malaysia.